From Foramina To Forensics: Mandibular Cbct Imaging In Gender Estimation - Patel , Twinkal; Dudhia, Bhavin; Kalaria, Setu; Bhatia, Parul; Patel, Purv; Virani, Rinkal (Journal of Neonatal Surgery, 2025)
Background and objectives: This study uses CBCT to determine gender based on the mandible, focusing on key landmarks like the mandibular foramen, canal, and mental and lingual foramina. Methods: Two hundred CBCT images of individuals aged 20-60 were analyzed for mandibular features using t-tests and logistic regression. Results: Gender differences were found in the posterior mandibular foramen, mandibular canal, mental foramen, lingual canal, and lingual foramen distances (p<0.05). Conclusion: This study underscores the relevance of CBCT in forensic odontology, providing nuanced insights into gender-related variations in mandibular anatomy.